2011
DOI: 10.1073/pnas.1013012108
|View full text |Cite
|
Sign up to set email alerts
|

Sulfiredoxin–Peroxiredoxin IV axis promotes human lung cancer progression through modulation of specific phosphokinase signaling

Abstract: Oxidative stress is known to cause tumorigenesis through induction of DNA and lipid damage. It also promotes cancer progression through a largely unknown mechanism. Sulfiredoxin (Srx) is a novel oxidative stress-induced antioxidant protein whose function in tumorigenesis and cancer progression has not been well studied. We report that Srx is highly expressed in human lung cancer. Knockdown of Srx reduces anchorage-independent colony formation, cell migration, and invasion of human lung cancer cells. Srx prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
116
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(120 citation statements)
references
References 34 publications
2
116
2
Order By: Relevance
“…Interestingly, modified (presumably oxidized) PrdxI accumulates in human lung cancer samples (Park et al 2006), indicating, perhaps, a role for the chaperone function of PrdxI in tumorigenesis (or elevated peroxide signaling). Furthermore, a recent study reported that increased Srx expression deregulates PrdxIV activity in lung cancers, and Srx and PrdxIV were found to be required for several key aspects of tumor growth and metastasis; e.g., anchorage-dependent colony formation, cell migration, and invasion (Wei et al 2011). In a previous study, increased Srx expression was observed also in several types of skin cancers (Wei et al 2008), indicating that deregulation of Prx activity may be involved in several types of human cancers.…”
Section: Links Between Chemotherapy Resistance and Prx Activitymentioning
confidence: 95%
“…Interestingly, modified (presumably oxidized) PrdxI accumulates in human lung cancer samples (Park et al 2006), indicating, perhaps, a role for the chaperone function of PrdxI in tumorigenesis (or elevated peroxide signaling). Furthermore, a recent study reported that increased Srx expression deregulates PrdxIV activity in lung cancers, and Srx and PrdxIV were found to be required for several key aspects of tumor growth and metastasis; e.g., anchorage-dependent colony formation, cell migration, and invasion (Wei et al 2011). In a previous study, increased Srx expression was observed also in several types of skin cancers (Wei et al 2008), indicating that deregulation of Prx activity may be involved in several types of human cancers.…”
Section: Links Between Chemotherapy Resistance and Prx Activitymentioning
confidence: 95%
“…We also detected increased 8-OHdG, suggestive of oxidative-and inflammationmediated DNA damage, in bladders of BBN-treated Sparc -/-mice compared with the Sparc +/+ ( Figure 4B). Because ROS results in lipid peroxidation and oxidation of proteins that contribute to carcinogenesis via activation of oncogenic transcription factors such as NF-κB and AP-1 (34,35), we determined the levels of lipid peroxidation product 8-isoprostane and found higher levels in Sparc -/-mice compared with their wild-type counterparts ( Figure 4C). Moreover, markers of protein oxidation, sulfiredoxin, and nicotinamide N-methyl transferase (NNMT) were significantly increased in bladder tumor tissues of Sparc -/-mice ( Figure 4D).…”
Section: Bladders Of Sparc -/-Mice Show Enhanced Accumulation Of Rosmentioning
confidence: 99%
“…Moreover, markers of protein oxidation, sulfiredoxin, and nicotinamide N-methyl transferase (NNMT) were significantly increased in bladder tumor tissues of Sparc -/-mice ( Figure 4D). Both have been correlated with progression and invasiveness of many cancers, including bladder (34,36).…”
Section: Bladders Of Sparc -/-Mice Show Enhanced Accumulation Of Rosmentioning
confidence: 99%
See 1 more Smart Citation
“…can also cause carcinogenesis through the induction of DNA damage and lipid dysregulation [86][87][88]. Indeed, the PRDX4 expression is variably high in most human malignant neoplasms, including prostate/lung adenocarcinoma or glioblastoma, and surprisingly, the suppression of PRDX4 leads to a significant reduction in tumor growth and/or metastatic potential [88][89][90][91][92][93]. In line with those findings, our data from clinical samples [10] show that patients with type 2 DM have significantly higher serum hPRDX4 levels than healthy adult volunteers, likely due to the greater demand for antioxidant defense in this chronic inflammatory disease.…”
Section: Prdx4 Exerts Beneficial Effects On Not Only the Hepatic But mentioning
confidence: 99%